Social science education under digital conditions: The role of creativity in media practices on social networks - Muschaweck, Isabelle; Falkenstein, David; Kanwischer, Detlef; Engartner, Tim (JSSE - Journal of Social Science Education, 2023)
Purpose: This paper explores social media practices with an exemplarily focus on constructions of space and social movements. It aims at identifying prospects for social science education under digital conditions regarding the reconfiguration of content and possibilities for digital literacy. Approach: By reviewing and summarizing popular strands of discussion on the application of social media practices in constructions of spaces and social movements, we identify common didactical themes from an educational perspective. Subsequently, we discuss social networks as real-world learning contexts in light of creative practices. Findings: Building on this, we derive theoretical implications for social science education for teaching and learning within social networks with a special focus on creativity. Following this, we present implications for social science literacy as well as digital literacy, which are two sides of the same coin. Practical implications: Finally, we present implications for future research and outline prospects for a future social science education.